The Character of Rip van Winkle: Representation of Disappearing Cultural Identity - Magdalena Baga (Univeristas Negeri Gorontalo, 2020)
Abstract ─ The purpose of this research is to explore how an ethnicity is represented in a story that has a historical setting and how this ethnic group was placed in American history. The short story of Washington Irving,